2009
DOI: 10.1007/s10571-009-9474-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Heterogeneity of Astrocyte De-Differentiation in vitro: Astrocytes Transform into Intermediate Precursor Cells Following Induction of ACM from Scratch-Insulted Astrocytes

Abstract: Our previous study definitely demonstrated that the mature astrocytes could undergo a de-differentiation process and further transform into pluripotential neural stem cells (NSCs), which might well arise from the effect of diffusible factors released from scratch-insulted astrocytes. However, these neurospheres passaged from one neurosphere-derived from de-differentiated astrocytes possessed a completely distinct characteristic in the differentiation behavior, namely heterogeneity of differentiation. The heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Previous investigations have demonstrated that activated neonatal mouse and rat astrocytes can be used to generate neurospheres 22,23 and are sensitized to neoplastic transformation after exposure to IR 41,42 . Furthermore, epidemiologic studies have established links between a variety of human malignancies and childhood exposure to ultraviolet and IR 4345 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have demonstrated that activated neonatal mouse and rat astrocytes can be used to generate neurospheres 22,23 and are sensitized to neoplastic transformation after exposure to IR 41,42 . Furthermore, epidemiologic studies have established links between a variety of human malignancies and childhood exposure to ultraviolet and IR 4345 .…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypically, this state of activation is characterized by elevated expression of intermediate filaments 12 , increased secretion of cytokines and extracellular matrix components 13 , cell hypertrophy 14 , proliferation 15 and migration 16 . Activated astrocytes also express elevated levels of the progenitor marker nestin 1719 , adopt a bipolar morphology 20,21 and can be used to generate neurospheres that are differentiable into neurons and oligodendrocytes 2224 . Together, these features are suggestive of a more primitive state of differentiation and recapitulate some of the phenotypic attributes of glioma cells 11,25 .…”
mentioning
confidence: 99%
“…30,31 The emergence of neural stem-like cells in the cortex was associated with the presence of GFAP and vimentin expressing cells, two intermediate filaments found in radial glial-like cells and in adult neural stem cells. [32][33][34] The existence of an astrocyte subpopulation that can acquire stem cell characteristics after injury has been described after an invasive CNS lesion, such as stab wounding or cerebral ischemia, but not after diffuse noninvasive injury.…”
Section: Discussionmentioning
confidence: 99%
“…One of such is a scratchwound assay (SW), first established as a simple, reproducible assay for the analysis of cell migration in vitro (13). The SW model was soon adopted by many to investigate different aspects of astroglial response to mechanical injury (14)(15)(16)(17). As a response to SW injury, the following characteristics of reactive astrocytes have been observed: hyperplasia, enhanced expression of extracellular matrix molecules and elongation of hypertrophic processes (18,19).…”
Section: Kratak Sadr`ajmentioning
confidence: 99%